Evasão fiscal no segmento de serviços de alimentação e alojamento: uma avaliação da Lei n. 13.975/07 - Pinheiro, Francisco José (2015)
The aim of this study was to analyze the efficiency of ◦ Law 13 975 of 14 September 2007. By this Act the Secretary of the Treasury of the State of Ceará can know the amount of sales by consumers who have paid off as the predominant form of payment credit card or debit card. Thus, I demanded, for part of the Treasury, extreme efficiency in relation to evasion of VAT taxpayers, especially in detecting possible and potential tax evaders. To this end, we used monthly series of collections of segments that make up the VAT in the State of Ceará, for the period November 2007 (date of implementation of the law) until December 2010. To test the effectiveness of the law outside the testing methodology employed econometric time series: it was the unit root test in order to analyze the order of integration of individual series, as well as the co-integration tests of Johansen (1990) pairwise between the alim series with all the series or not using a credit card or debit card. We conclude that the results of the study did not find sufficient evidence to reducing tax evasion. Furthermore, the number of food (alim) proved to be co-integrated more with the series that do not use credit or debit card than with those using a credit card or debit card.